Knowledge Regarding Urinary Tract Infection (UTI) and Its Prevention during Pregnancy among Antenatal Mothers - Ms. Megha Chaugale; Ms Chandrala S Patole; Ms. Mrudula Lagare; Ms. Mayavati Gaikwad; Mr. Prasad Ghatge; Mr. Prashant Kumbhar; Mr. Prathmesh Shinde; Mr. Pushkaraj Dangi (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background and Objective: UTI ranks as the second most frequent bacterial infection and is the most prevalent bacterial disease among pregnant women. It is estimated that around one out of every three women will likely face a UTI at some point. Approximately 8.3 million pregnant women worldwide experience UTIs annually. This increase in prevalence is attributed to the enlargement and additional weight of the uterus, which disrupts normal bladder function and results in symptoms such as incomplete voiding, urine dribbling, and frequent urination. Urinary tract infections in pregnant women can give rise to various complications, including the delivery of infants with low birth weight, an increased risk of abortion, preterm birth, development of preeclampsia, preterm labor, stillbirth, chronic pyelonephritis, and, in rare cases, kidney failure. While the likelihood of developing acute episodes of UTI is relatively low in the early stages of pregnancy, there is a significant increase in risk during the final trimester, ranging from 30 %–60 %. Neglecting early treatment of a UTI can have adverse consequences on the well-being of the baby. Objectives of the Study: 1. To assess the knowledge regarding Urinary tract infection (UTI) and its prevention during pregnancy among antenatal mothers. 2. To find out an association between knowledge regarding Urinary tract infection (UTI) and its prevention during pregnancy among antenatal mothers with their selected socio-demographic variables. Methods: The research approach adopted for the study was quantitative evaluative Survey approach. Research design was Non experimental, Descriptive quantitative evaluative design. Ethical clearance was obtained from the institution. Formal administration permission was obtained from the medical officer of Shiroli PHC. Then 80 antenatal mothers were selected by using non probability purposive sampling technique. An informed consent was obtained from the participants. In order to obtain a free and true response, the purpose and importance of the study was explained to selected samples. The main study was conducted at Shiroli PHC, Kolhapur from the 04/01/2025 to 10/01/2025. Data collection was done as per the timings provided by the Medical officer. Researchers introduced themselves to the samples. Explained the purposes and objectives of the study. Samples were taken into confidence and assured of confidentiality of their data identity and their responses. Average time were given for solve the questionnaire that is 30 min approximately. Results: A majority 42 (53%) have good knowledge, indicating strong understanding of the subjects, while 21 (26%) possess an average level of knowledge, reflecting moderate understanding. The remaining 17 (21%) were categorized under poor knowledge. There was statistical significant association between knowledge scores of subjects with their selected socio-demographic variable i.e. Education [χ2cal= 18.73, χ2tab= 9.44]. The calculated chi square value was higher than tabulated value. The calculated Chi-square values for type Education was greater than tabulated value at p < 0.05 level of significance. Hence H1 was accepted. Interpretation And Conclusion: The present study revealed that a majority 42 (53%) have good knowledge, indicating strong understanding of the subjects, while 21 (26%) possess an average level of knowledge, reflecting moderate understanding. The remaining 17 (21%) were categorized under poor knowledge.